Sex in Revolution Gender, Politics, and Power in Modern Mexico - Ann, Blum; Anne, Rubenstein; Cano, Gabriela; Carlos, Monsiváis; Gabriela, Cano; Heather, Salami; Jocelyn, Olcott; Julia, Tuñón; Kristina, Boylan; Lynn, Stephen; Mary, Vaughan; María, Aceves; et al. (Duke University Press, 2007)
Sex in Revolution challenges the prevailing narratives of the Mexican Revolution and postrevolutionary state formation by placing women at center stage. Bringing to bear decades of feminist scholarship and cultural approaches to Mexican history, the essays in this book demonstrate how women seized opportunities created by modernization efforts and revolutionary upheaval to challenge conventions of sexuality, work, family life, religious practices, and civil rights.Concentrating on episodes and phenomena that occurred between 1915 and 1950, the contributors deftly render experiences ranging from those of a transgendered Zapatista soldier to upright damas católicas and Mexico City's chicas modernas pilloried by the press and male students. Women refashioned their lives by seeking relief from bad marriages through divorce courts and preparing for new employment opportunities through vocational education.